Pengaruh Display Product Dan Price Discount Di Masa Pandemic Covid-19 Terhadap Impulse Buying Produk Food Supermarket (Studi Pada Konsumen Toserba Yogya Ciranjang) - Intan Rike Febriyanti; Galih Raspati; Umban Adi Jaya; Andika Aryadinata Aryadinata (Institut Manajemen Wiyata Indonesia, 2021)
This study aims to determine the effect of Display Product and Price Discount on Impulse Buying of food supermarket products. This study uses an associative quantitative approach using a questionnaire distributed to 100 samples with purposive sampling technique that has criteria as consumers of yogya Ciranjang department stores. The instrument testing in this study used validity and reliability tests, data analysis techniques used descriptive analysis, used the classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test, and multiple linear regression analysis consisting of hypothesis testing (t test and F test). ) and analysis of the coefficient of determination (R2). The results of this study indicate that: (1) Display Product has a positive effect on Impulse Buying of supermarket food products, as evidenced by the t value of 2.129 and the regression coefficient has a positive value of 0.149; (2) Price Discount has a positive effect on Impulse Buying for food supermarket products, as evidenced by the t count value of 4.471 and the regression coefficient has a positive value of 0.315; and (3) Product Display and Price Discounts have a positive effect on Impulse Buying for food supermarket products, as evidenced by the F count result of 27.425 with a significance of 0.000. (4) The magnitude of the effect of Display Product and Price Discount on Impulse Buying of supermarket food products is evidenced by the adjusted R square value of 0.348 indicating that the ability of the independent variable in explaining the variation of the dependent variable is 34.8% and the remaining 65.2% is explained by the variable others outside of this research model